Births and their outcomes by time, day and year: a retrospective birth cohort data linkage study - Alison Macfarlane; Nirupa Dattani; Rod Gibson; Gill Harper; Peter Martin; Miranda Scanlon; Mary Newburn; Mario Cortina-Borja (National Institute for Health Research, 2019)
Background: Studies of daily variations in the numbers of births in England and Wales since the 1970s have found a pronounced weekly cycle, with numbers of daily births being highest from Tuesdays to Fridays and lowest at weekends and on public holidays. Mortality appeared to be higher at weekends. As time of birth was not included in national data systems until 2005, there have been no previous analyses by time of day. Objectives: To link data from birth registration and birth notification to data about care during birth and any subsequent hospital admissions and to quality assure the linkage. To use the linked data to analyse births and their outcomes by time of day, day of the week and year of birth. Design: A retrospective birth cohort analysis of linked routine data. Setting: England and Wales. Outcome measures: Mortality of babies and mothers, and morbidity recorded at birth and any subsequent hospital admission. Population and data sources: Birth registration and notification records of 7,013,804 births in 2005-14, already linked to subsequent death registration records for babies, children and women who died within 1 year of giving birth, were provided by the Office for National Statistics. Stillbirths and neonatal deaths data from confidential enquiries for 2005-9 were linked to the registration records. Data for England were linked to Hospital Episode Statistics (HES) and data for Wales were linked to the Patient Episode Database for Wales and the National Community Child Health Database. Results: Cross-sectional analysis of all births in England and Wales showed a regular weekly cycle. Numbers of births each day increased from Mondays to Fridays. Numbers were lowest at weekends and on public holidays. Overall, numbers of births peaked between 09.00 and 12.00, followed by a much smaller peak in the early afternoon and a decrease after 17.00. Numbers then increased from 20.00, peaking at around 03.00-05.00, before falling again after 06.00. Singleton births after spontaneous onset and birth, including births in freestanding midwifery units and at home, were most likely to occur between midnight and 06.00, peaking at 04.00-06.00. Elective caesarean births were concentrated in weekday mornings. Births after induced labours were more likely to occur at hours around midnight on Tuesdays to Saturdays, irrespective of the mode of birth. Limitations: The project was delayed by data access and information technology infrastructure problems. Data from confidential enquiries were available only for 2005-9 and some HES variables were incomplete. There was insufficient time to analyse the mortality and morbidity outcomes. Conclusions: The timing of birth varies by place of birth, onset of labour and mode of birth. These patterns have implications for midwifery and medical staffing. Future work: An application has now been submitted for funding to analyse the mortality outcomes and further funding will be sought to undertake the other outstanding analyses. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 7, No. 18. See the NIHR Journals Library website for further project information.